Comparison of fast flow and initial slope index values for cerebral blood flow following subarachnoid haemorrhage. Issue 4 (April 1986) - Richards, P G; Tsutsui, T; Symon, L; Jabre, A; Rosenstein, J; Redmond, S
Abstract : Forty five patients with subarachnoid haemorrhage proved by lumbar puncture underwent serial measurements of cerebral blood flow and central conduction time. When the initial slope index (ISI) value for cerebral blood flow is considered there is a clear relationship between reduction of cerebral blood flow and deteriorating clinical grade. This relationship is not so clearly demonstrated using the fast flow (f1) value for cerebral blood flow. When cerebral blood flow is compared to central conduction time those patients with a central conduction time longer than 6 X 4 ms have a significantly lower CBFisi but not a significant lower CBFf1. Furthermore, using the ISI value, there is a linear relationship between the fall in cerebral blood flow and the lengthening of CCT below a threshold blood flow of about 35 ml/100 g/min. This relationship is not demonstrated with the CBFf1 value. It therefore appears that the ISI value for cerebral blood flow shows a greater correlation between clinical and electrophysiological events than the f1 value.